Towards Indigenous Policy and Practice: A Tuvaluan Framework for Wellbeing, Ola Lei - Panapa, Tufoua; Park, Julie; Littleton, Judith; Chambers, Anne; Chambers, Keith (Waka Kuaka, 2021)
Ola Lei ‘wellbeing’ is an ethnographically derived framework that builds upon Tuvaluan cultural concepts and practices. It has value as a conceptual model by which to assess and build health, education and development initiatives. Te feke ‘the octopus’ represents what Tuvaluans think and do about wellbeing, based on ethnographic research by the first author. Like the octopus, this framework is dynamic and adaptable, illustrating how wellbeing intertwines with social, cultural, economic and spiritual life, with education, with land and ocean. After describing the components of Ola Lei and how they were derived from participant observation and interviews, we suggest applications in policy and practice. The Ola Lei Framework articulated here provides an example of scholars taking indigenous concepts seriously as theory.